Community-Based Homestay Management in the Village Tourism of Tete Batu, Lombok - Sugandi, Yogi Birrul Walid; Paturusi, Syamsul Alam; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
The dynamics of homestay development in the village tourism in Lombok is very rapid after the launching of 99 village tourisms by the West Nusa Tenggara Government. Homestay is one of the ways to get benefits of tourism by local community. Otherwise, the operation of homestays, especially in Tete Batu has impacted on three main problems: the welfare distribution is not easy to achieve, conflicts of interest, homestay programs are not well organized. This research aimed to produce community-based homestay management strategies. This study used a qualitative method with SWOT analysis. Data collection was done by observation, interviews, documentation, literature studies, and FGDs. There were 17 informants deliberately chosen. The results showed that the position of the homestay was in strong internal and external conditions. The right grand strategies to apply are market penetration, market development, product management and development. The combination strategy results are as follows: establishing and strengthening of homestay institutions, making integrated tour packages, optimizing online promotional content, procuring digital system, improving environmentally friendly villages, increasing the qualied human resources, maintaining the authenticity of nature and traditions, creating variety of new tourist attractions, increasing community empowerment, forming the synergy of pentahelix. Keywords: Homestay Management, Village tourism, Community-Based Tourism